SPECT/CT in Postoperative Painful Hip Arthroplasty - Van Den Wyngaert, Tim; Paycha, Frederic; Strobel, Klaus; Kampen, Willm Uwe; Kuwert, Torsten; Van Der Bruggen, Wouter; Gnanasegaran, Gopinath (Seminars in Nuclear Medicine, 2018)
Consecutive milestones in hip arthroplasty design and surgical technique have contributed to the successful and cost-effective intervention this procedure has become today in maintaining mobility and quality of life in patients with osteoarthritis, fracture, or other hip conditions. With the increasing prevalence of hip joint replacements, the need for improved diagnostic imaging tools to guide revision surgery has risen in parallel. Over the last few years, promising data have emerged on the potential role of bone SPECT/CT imaging in the assessment of patients with recurrent pain after arthroplasty. This review summarizes the trends in hip arthroplasty surgery (partial vs total arthroplasty; cemented vs cementless arthroplasty; resurfacing arthroplasty) and prosthesis design (bearing materials; stem designs) over the last decade. In particular, the impact on the biomechanics and interpretation of bone SPECT/CT findings is discussed, with emphasis on integrative reporting in the following frequently encountered conditions: lysis/aseptic loosening, septic loosening, heterotopic ossification, periprosthetic fracture, tendinopathies, and adverse local tissue reactions. Based on the available literature data, bone SPECT/CT is increasingly being used as second-line imaging modality when conventional investigations are nondiagnostic. Further outcome research is warranted to examine whether this technique could be used earlier in patient management.
EVALuna2:212300